A Simple Approach to Incorporating STATCOM into a Newton-Based Power Flow and Optimal Power Flow Algorithms - Muyideen Olalekan Lawal (Journal of Electrical Technology UMY, 2023)
Incorporating STATCOM into existing power flow (PF) or optimal power flow (OPF) algorithm usually requires the development of complex program codes to represent associated derivatives introduced by STATCOM power flow models. This procedure is time consuming as it may require various corrections of errors before having a suitable program that effectively solves the problem. To avoid this stress, an efficient way of incorporating STATCOM’s power flow models into an existing Newton-based PF and OPF algorithm is presented in this paper. These models introduce the magnitude and angle of the STATCOM’s source converter’s voltage as a state variable into the PF and OPF problem formulations. This work simply treats the STATCOM as a PV-bus with zero real power in existing PF and OPF algorithms. The proposed procedures were applied to a 5-bus test system and the results obtained were validated with similar works available in open literature. After a satisfactory performance, it was further applied to the 30-bus and 57-bus IEEE test systems. The results obtained show the effectiveness of the proposed procedures in voltage profile improvement. For example, the PF results show that the voltage magnitudes of the two buses with STATCOM in the 30-bus system were improved from 0.9881 pu and 0.9702 pu to 1.027 pu and 1.041 pu, respectively. Also, the OPF results show that the voltage magnitudes of the three buses with STATCOM in the 57-bus system were improved from 1.063 pu, 0.90 pu and 0.9683 pu to 1.039 pu, 0.9796 pu and 1.0144 pu, respectively.